Peningkatan Kapasitas Adaptif dan Pendampingan Pengelolaan Kesehatan Masyarakat Terhadap Risiko Perubahan Iklim di Desa Reuleut Timu Kabupaten Aceh Utara - Khairunnisa, Khairunnisa; Darwis, Aryandi; Zahrina, Zahrina; Nabiilah, Anis En; Chairunnissa, Chairunnissa; Fathiyyah, Najla (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
Climate change is currently a hot topic at both the global and national levels. Various events related to climate change, such as extreme rainfall, increasing air temperatures, rising sea levels, and increasing pollutant concentrations, have an impact on increasing the intensity of disasters that can cause economic and environmental losses, and the average temperature on the earth's surface will increase by 3-5 degrees Celsius. The general objective of this community service activity is to increase public knowledge and preparedness in facing the impacts of climate change on health through education, training, and community-based interventions. Direct and interactive outreach and training activities make it easier for the community to understand the concept of health adaptation to climate. Following this outreach activity, monitoring and evaluation are also carried out regarding the capacity of health cadres in the use of health equipment and the growth of plant seedlings as an environmental intervention in facing the impacts of climate change. Tree planting reflects the integration between public health efforts and environmental conservation.